The mitochondrial dicarboxylate and 2‐oxoglutarate carriers do not transport glutathione. Issue 5 (28th January 2015) - Booty, Lee M.; King, Martin S.; Thangaratnarajah, Chancievan; Majd, Homa; James, Andrew M.; Kunji, Edmund R.S.; Murphy, Michael P.
Abstract : Glutathione carries out vital protective roles within mitochondria, but is synthesised in the cytosol. Previous studies have suggested that the mitochondrial dicarboxylate and 2‐oxoglutarate carriers were responsible for glutathione uptake. We set out to characterise the putative glutathione transport by using fused membrane vesicles of Lactococcus lactis overexpressing the dicarboxylate and 2‐oxoglutarate carriers. Although transport of the canonical substrates could be measured readily, an excess of glutathione did not compete for substrate uptake nor could transport of glutathione be measured directly. Thus these mitochondrial carriers do not transport glutathione and the identity of the mitochondrial glutathione transporter remains unknown. Abstract : Dicarboxylate or 2‐oxoglutarate carriers are expressed in Lactococcus lactis . Glutathione is not a competitive substrate of dicarboxylate or 2‐oxoglutarate carriers. Dicarboxylate and 2‐oxoglutarate carriers do not transport glutathione. The identity of the mitochondrial glutathione transporter is unknown.